Association between periodontal disease and chronic obstructive pulmonary disease - Peiya Lin; Anhao Liu; Yosuke Tsuchiya; Kanako Noritake; Yujin Ohsugi; Keita Toyoshima; Yuta Tsukahara; Takahiko Shiba; Hiroshi Nitta; Akira Aoki; Takanori Iwata; Sayaka Katagiri (Elsevier, 2023)
Chronic obstructive pulmonary disease (COPD) and periodontal disease are chronic inflammatory conditions that significantly affect an individual's overall health and well-being. Generally, the prevalence of periodontitis is higher in patients with COPD than those without COPD, which may partly be attributed to common risk factors in COPD, such as smoking, respiratory infections, and inflammation. In particular, periodontitis may exacerbate the progression of COPD and further deteriorate the respiratory system by promoting inflammatory responses and bacterial infections. Immunocytes, including neutrophils, and microorganisms such as Fusobacterium nucleatum originating from oral biofilms are believed to be crucial factors influencing to COPD. Furthermore, the potential benefits of treating periodontal disease in COPD outcomes have been investigated. Although the relationship between COPD and periodontal disease has been preliminarily studied, there is currently a lack of large-scale clinical studies to validate this association. In addition to clinical examinations, investigating biomarkers and microbiology may contribute to explore the underlying mechanisms involved in the management of these conditions. This review aims to contribute to a better understanding of the clinical and basic research aspects of COPD and periodontitis, allowing for potential therapeutic approaches and interdisciplinary management strategies.